A Case on the Project Failure of Water Vending Machines of Indian Railways : Financial Concerns and Beyond - Manna, Atanu; Pahari, Subhajit; Rana, Sudhir; Biswas, Debasish (Prabandhan: Indian Journal of Management, 2023)
The provision of clean water in remote areas and public places is crucial for public health. The Indian Railways implemented a revolutionary project to install water vending machines (WVM) on railway platforms to provide affordable water access to passengers. However, after 5 years of implementation, the project failed, leaving many questions unanswered. This study aimed to explore the factors associated with the project’s failure and its probable solutions. The study used the Socio-Ecological Model (SEM) and Fishbone diagram to categorize the factors and their plausible solutions. Seventeen interviews were conducted with railway staff, operators, and passengers using a semi-structured questionnaire. The study identified six significant factors associated with the project’s failure: machine and equipment-related issues, people and management-related concerns, financial concerns, maintenance and repair issues, communication and delegation issues, and environmental concerns. The study recommended awareness enhancement at the intrapersonal level and operator training at the interpersonal level to address the project’s challenges. Communication improvement and delegation of authorities at the institutional and community level, effective policy implementation, and sustainability awareness are essential to enhance the project’s efficiency. Multilevel problem analysis is crucial before implementing any project to reduce uncertainty and improve its efficiency. Besides highlighting the factors associated with the failure of the WVM project implemented by the Indian Railways, the findings and recommendations of this study will be beneficial to project managers in the future, helping them to overcome the challenges associated with similar projects and make them more viable.